2017
DOI: 10.1016/j.stemcr.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Craniometaphyseal Dysplasia Mutations in ANKH Negatively Affect Human Induced Pluripotent Stem Cell Differentiation into Osteoclasts

Abstract: SummaryWe identified osteoclast defects in craniometaphyseal dysplasia (CMD) using an easy-to-use protocol for differentiating osteoclasts from human induced pluripotent stem cells (hiPSCs). CMD is a rare genetic bone disorder, characterized by life-long progressive thickening of craniofacial bones and abnormal shape of long bones. hiPSCs from CMD patients with an in-frame deletion of Phe377 or Ser375 in ANKH are more refractory to in vitro osteoclast differentiation than control hiPSCs. To exclude differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Osteoclasts in mutant mice and CMD patients are reduced in numbers, have defective actin rings, and have decreased resorptive activity, which greatly contributes to the skeletal phenotype of CMD. (11,12) Despite advances in CMD research, the pathogenesis remains not fully elucidated. Treatment is still limited to surgical decompression of obstructed foramina and to plastic surgery for correcting craniofacial structures.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclasts in mutant mice and CMD patients are reduced in numbers, have defective actin rings, and have decreased resorptive activity, which greatly contributes to the skeletal phenotype of CMD. (11,12) Despite advances in CMD research, the pathogenesis remains not fully elucidated. Treatment is still limited to surgical decompression of obstructed foramina and to plastic surgery for correcting craniofacial structures.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ANKH protein levels were strongly reduced in osteoblast-like cells derived from bone explant cultures and in stem cells from human exfoliated deciduous teeth (SHEDs) from CMD patients with ANKH_F377del compared to cells from control individuals (Fig. 1C ) 22 . Cell lysate from Ank KO/KO osteoclasts served as negative control for antibody binding (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Furthermore, there are reports that proteasomal inhibitors and the lysosomal inhibitor bafilomycin a1 can suppress osteoclast function 39 , 40 , although other studies suggest that proteasomal inhibitors may induce osteoclast survival and formation 41 . Previously we reported deficient osteoclastogenesis in the CMD mouse model and in CMD patients, which is in part responsible for hyperostosis of craniofacial bones 18 , 22 . In addition, bortezomib has been shown to enhance bone formation, partly by modulating runt-related transcription factor 2 (Runx2) 42 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Cx43 are required for osteoblast and osteoclast differentiation and function [84], and the compromised Cx43 could significantly limit the cell-cell communication needed for osteoclastogenesis and bone remodeling. Studies showed that hiPSCs with ANKH mutations formed fewer osteoclasts, expressed lower levels of osteoclast specific genes, and resorbed less bone [85].…”
Section: Ipscs Derived From Patients With Skeletal Disordersmentioning
confidence: 99%